Agrarian Elites and Italian Fascism : The Province of Bologna, 1901-1926 - Cardoza, Anthony L., 1947- (Book collections on Project MUSE., 1982)
Treating the tumultuous period from 1901 to the late 1920s, this book describes social and political conflict in the cradle of agrarian fascism.Originally published in 1983.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.